2005
DOI: 10.1042/bj20051076
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking defects of the Southeast Asian ovalocytosis deletion mutant of anion exchanger 1 membrane proteins

Abstract: Human AE1 (anion exchanger 1) is a membrane glycoprotein found in erythrocytes and as a truncated form (kAE1) in the BLM (basolateral membrane) of a-intercalated cells of the distal nephron, where they carry out electroneutral chloride/bicarbonate exchange. SAO (Southeast Asian ovalocytosis) is a dominant inherited haematological condition arising from deletion of Ala400-Ala408 in AE1, resulting in a misfolded and transport-inactive protein present in the ovalocyte membrane. Heterozygotes with SAO are able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 52 publications
8
32
0
Order By: Relevance
“…Various approaches (e.g., see references [89,90]) generally have yielded similar conclusions about the amino acid residues that contribute to transmembrane segments 1 through 5 (TM1 through TM5). Therefore, investigators feel reasonably confident about these assignments.…”
Section: Other Members Of the Slc4 Familymentioning
confidence: 86%
“…Various approaches (e.g., see references [89,90]) generally have yielded similar conclusions about the amino acid residues that contribute to transmembrane segments 1 through 5 (TM1 through TM5). Therefore, investigators feel reasonably confident about these assignments.…”
Section: Other Members Of the Slc4 Familymentioning
confidence: 86%
“…Disruption of chaperone interactions may allow for the release of ER-retained membrane glycoproteins and permit their trafficking to the cell surface. We have demonstrated previously that dominant dRTA kAE1 mutants are retained in the ER when expressed in HEK-293 and MDCK cells (14,15). We also have shown that erythroid AE1 is able to interact with calnexin in a glycosylation-dependent manner both in vitro and in HEK and K562 cells (22,23).…”
mentioning
confidence: 85%
“…Immunofluorescence and Microscopy-Immunofluorescence staining and confocal microscopy of MDCK cells stably expressing kAE1 was performed as described previously (15). Imaging equipment includes a laser scanning confocal Zeiss LSM 510 microscope, Zeiss AxioCam, AxioVision, and LSM image browser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oligosaccharide on AE1 in HEK-293 cells remains in the high mannose form and is sensitive to digestion with endoglycosidase H. At steady state, about 30% of wild type AE1 in the high mannose form is present at the cell surface with the remainder in the ER (25). The expression of SAO and HS R760Q in HEK-293 cells results in their intracellular retention in the ER (23,26); however, no enhanced interaction of chaperones with the mutants relative to the wild type protein was detected by co-immunoprecipitation (supplemental Fig. S2).…”
Section: Ae1 and Mutants Can Interact With Cnx In Vivo-mentioning
confidence: 99%